Level of health literacy in Latvia and Lithuania: a population-based study - Ieva Gatulytė; Valērija Verdiņa; Zane Vārpiņa; Ágnes Lublóy (BMC, 2022)
Abstract Background Measuring and understanding the level of health literacy serves as a starting point for developing various policies in health care. The consequences of weak health literacy competencies are severe; they result in riskier health behaviour, poorer health status, more frequent emergency visits and hospitalizations. This research has three aims: i) measure the level of health literacy in the populations of Latvia and Lithuania; ii) investigate which demographic and socioeconomic determinants are associated with it; and iii) discuss the means of improving its current level. Methods We employ a validated survey tool, the 47-item European Health Literacy Questionnaire (HLS-EU-Q). In addition to the 47 questions in the domains of health care, disease prevention, and health promotion, the participants' demographic and socioeconomic characteristics are assessed. Face-to-face paper-assisted surveys are conducted with randomly selected residents from Latvia and Lithuania. The level of health literacy is measured by the health literacy index. Spearman correlation analyses and multiple regressions models are employed for investigating the association between the health literacy level and its determinants. The survey tool is complemented with in-depth interviews with six healthcare industry experts in order to assess the most promising ways to improve the level of health literacy. Results The stratified random sampling with quota elements assured a representative sample in terms of gender, urban/rural distribution and regions. In Latvia, 79% of the population possesses weak health literacy competencies. In Lithuania, 73% of the population can be characterized with inadequate or problematic level of health literacy. The most important determinants of the health literacy level include age, financial situation, social status, and ethnicity. In particular, elderly (aged 76 and over) and the Latvian-speaking population are less health literate, while those having better financial situation and higher social status are more health literate. The three most promising ways to improve the level of health literacy, as suggested by the healthcare industry experts, include health education in schools, provision of structured health-related information in Latvian and Lithuanian, and guidelines for the most common health problems. Conclusions The proportion of population with inadequate or problematic level of health literacy is higher in Latvia and Lithuania than in several other European countries. There is an urgent need to develop policies to improve it.